Acupuncture for dry eye: a randomised controlled trial protocol - Kim, Tae-Hun (BioMed Central, 2009)
BACKGROUND: Dry eye is usually managed by conventional medical interventions such as artificial tears, anti-inflammatory drugs and surgical treatment. However, since dry eye is one of the most frequent ophthalmologic disorders, safer and more effective methods for its treatment are necessary, especially for vulnerable patients. Acupuncture has been widely used to treat patients with dry eye. Our aim is to evaluate the effectiveness and safety of acupuncture for this condition. METHODS/DESIGN: A randomised, patient-assessor blinded, sham (non-acupuncture point, shallow acupuncture) controlled study was established. Participants allocated to verum acupuncture and sham acupuncture groups will be treated three times weekly for three weeks for a total of nine sessions per participant. Seventeen points (GV23; bilateral BL2, GB4, TE23, Ex1 (Taiyang), ST1 and GB20; and left SP3, LU9, LU10 and HT8 for men, right for women) have been selected for the verum acupuncture; for the sham acupuncture, points have been selected that do not coincide with a classical acupuncture point and that are located close to the verum points, except in the case of the rim of the eye. Ocular surface disease index, tear film breakup time, the Schirmer I test, medication quantification scale and general assessment of improvement will be used as outcome variables for evaluating the effectiveness of acupuncture. Safety will also be assessed at every visit. Primary and secondary outcomes will be assessed four weeks after screening. All statistical analyses will be performed using analysis of covariance. DISCUSSION: The results of this trial will be used as a basis for clarifying the efficacy of acupuncture for dry eye. TRIAL REGISTRATION: ClinicalTrials.gov NCT00969280.